Peningkatan Aktivitas dan Hasil Belajar Siswa melalui Implementasi Model Pembelajaran Problem Based Learning Pada Materi Keanekaragaman Hay - Yusnaeni, Yusnaeni; Ayu R., Natonis (Media Sains, 2024)
This Classroom Action Research aims to the quality of learning as meassured through student learning activities, teacher teaching activities and student learning outcomes through the implementation of the Problem Based Learning model to biodiversity material in class X MIPA 2 SMA Kristen 2 Soe. The research subject were 34 people consisting of 14 male and 20 female. The reseacrh was carried out in 2 cycles, each cycle consisting of planning, action and observation, adn reflection stages. Data collection was carried out through test and observation techniques. The data collection instruments used were teacher and student activity observation sheet instrument, and test instruments in the form of pretest anf posstest questions. The research result obtained : 1) student activity based on observation result increased by 30,36%, 2) teacher activity observation result increased by 7,96%, 3) Student learning outcomes increased by 24,76%. These result indicate that the implementation of the Problem Based Learning model can increase teacher and student activities as well as student learning outcomes in the learning process.